Peran Negara dalam Menjamin Hak Asasi Manusia Menurut Hukum Tata Negara Islam - Auliah Ramadhani; Nurkholis Ali Ridho; Kurniati Kurniati (Jurnal Ilmu Sosial dan Humaniora, 2026)
Human rights are fundamental rights inherent in every individual and serve as the foundation for a just state governance system. In the perspective of Islamic constitutional law, human rights are rooted in sharia principles aimed at achieving public welfare. This study aims to analyze the concept of human rights in Islamic constitutional law and examine the role of the state in guaranteeing, protecting, and enforcing these rights. The research employs a normative juridical approach by reviewing legal doctrines, Islamic legal principles, and relevant regulations. The findings indicate that human rights in Islam encompass both moral and legal dimensions, interconnected through the principles of huququl ibad and maqashid al-shariah. The state plays a strategic role as a protector and guarantor of rights through a fair, transparent, and non-discriminatory legal system. Furthermore, the implementation of human rights in Indonesia reflects the substantive integration of Islamic values within the constitutional framework and public policies. However, challenges remain in harmonizing sharia values with modern human rights standards. Therefore, strengthening the role of the state and public awareness is essential to ensure optimal human rights protection.